Análise da adição de resíduo oriundo do tratamento de esgotos em massa cerâmica utilizada para fabricação de telhas - Lima, Andressa Dantas de (2009)
Sludge of Wastewater Treatment Plants (WTPs) disposal is a problem for any municipality, for this reason the amount of sludge production is now a key issue in selecting treatment methods. It is necessary to investigate new applications for this waste type, due to the restrictions imposed by the environmental organs. The raw materials used in the Red Ceramic, are generally very heterogeneous, for this reason, such materials can tolerate the presence of different types of wastes. In Rio Grande do Norte, the roof tiles production corresponds to 60,61% from the total of ceramic units produced. Due to the importance of the ceramic industry of roof tiles for the state, allied to the environmental problem of the sludge disposal, this work had for objective to verify the possibility of the incorporation of sewage sludge in ceramic body used for production of roof tiles. In the research, sludge originating from drying beds of WTP of the Central Campus from UFRN and clays originating from a ceramic industry from Goianinha/RN were used. The raw materials were characterized by techniques of: analysis of particles distribution by diffraction to laser; real density; consistence limits; chemical analysis by X-ray fluorescence; mineralogical analysis by X-ray diffraction; organic matter; and solids content. Five batches of roof tiles were manufactured in the approximate dosages of 2%, 4%, 6%, 8% and 10%. To evaluate the properties of each final product, tests of water absorption, impermeability, bending strength, leachability and solubility were accomplished. The roof tiles manufactured with sludge presented characteristics similar to the roof tiles without sludge in relation to the environmental risk. The results showed that it is possible to use approximately up to 4% of sludge in ceramic bodies for production of roof tiles. However, it is observed that the high amount of organic matter (71%) present in the sludge is shown as factor that limits the sludge incorporation in ceramic bodies, worsening the quality of the roof tiles. It is necessary the use of mixtures of different raw materials under point of view of the granulometry and of the other chemical and mineralogical properties for the obtaining of a satisfactory mass to the production of ceramic roof tiles